Trauma in adult and higher education : conversations and critical reflections - Douglass, Laura; Threlkeld, Aubry, 1980-; Merriweather, Lisa R. (Adult learning in professional, organizational, and community settings., 2022)
"Trauma in Adult and Higher Education: Conversations and Critical Reflections invites readers to think deeply about the experiences of trauma they witness in and outside of the classroom because trauma alters adult learners' experience by disrupting identity, and interfering with memory, relationships and creativity. Through essays, narratives, and cultural critiques, the reader is invited to rethink education as more than upskilling and content mastery; education is a space where dialogue has the potential to unlock an individual's sense of power and self-mastery that enables them to make sense of violence, tragedy and trauma. Trauma in Adult and Higher Education: Conversations and Critical Reflections reveals the lived experiences of educators struggling to integrate those who have experienced trauma into their classrooms - whether this is in prison, a yoga class, or higher education. As discourses and programming to support diversity intensifies, it is central that educators acknowledge and respond to the realities of the students before them. Advocates of trauma-sensitive curriculum acknowledge that trauma shows up as a result of the disproportionate amount of violence and persistent insecurity that specific groups face. Race, gender, sexual orientation, ability, and immigration are all factors that expose individuals to higher levels of potential trauma. Trauma has changed the conversations about what education is, and how it should happen. These conversations are resulting in new approaches to teaching and learning that address the lived experiences of pain and trauma that our adult learners bring into the classroom, and the workforce. This collection includes a discussion of salient implications and practices for adult and higher education administrators and faculty who desire to create an environment which includes individuals who have experienced trauma, and perhaps prevents the cycle of violence"--